2014
DOI: 10.1155/2014/636493
|View full text |Cite
|
Sign up to set email alerts
|

Primary Otomycosis in the Indian Subcontinent: Predisposing Factors, Microbiology, and Classification

Abstract: Objective. To define otomycosis and determine the predisposing factors and microbiology in primary otomycosis. Study Design. Prospective study of two years and review of the literature. Setting. Academic Department of Otolaryngology in a coastal city in India. Patients. 150 immunocompetent individuals of whom 100 consecutive patients with a clinical diagnosis of otomycosis are considered as the study group and 50 consecutive patients with no otomycosis are considered as the control group. Results and Observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
60
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 34 publications
(89 reference statements)
10
60
3
3
Order By: Relevance
“…In most of the studies otomycosis involves only one and mostly the right ear. 2,12,14 In this study unilateral otomycosis was seen in 73.78% patients complimenting the already reported observations. This phenomenon is believed to be due to the right handedness of most of the patients with habit of ear poking, but same findings are not found in other studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In most of the studies otomycosis involves only one and mostly the right ear. 2,12,14 In this study unilateral otomycosis was seen in 73.78% patients complimenting the already reported observations. This phenomenon is believed to be due to the right handedness of most of the patients with habit of ear poking, but same findings are not found in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…The condition is more common in males and same pattern is noted in current series. 2,4,12,13 The possible reason may be more exposure of males to fungal spores due to outdoor work. In most of the studies otomycosis involves only one and mostly the right ear.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,12 Studies from Karnataka and Pakistan have reported it to be more common in males as in our study. 1,6,7,13 whereas studies from Nigeria, Brazil, Iran, Shanghai and Haryana have reported it to be more common among young females. 2.14 In our series, the ratio was 1.04:1.…”
Section: Age Sex and Occupationsupporting
confidence: 65%
“…The case control study was planned because fungi are also isolated from healthy ears. 6 Approval from the Institutional Ethical and Research Committee was obtained before conducting the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation